Factors influencing the identification and development of Australian female tennis talent - Young, J.; Pearce, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Talent Identification and Talent Development are complementary and challenging activities underpinning National Sporting Organisations` pursuits to facilitate sporting excellence. In the sport of tennis, it is usually parents who identify the first signs of talent in their children. A combination of factors is subsequently thought to be important for the development of such talent, with parents and coaches playing dominant roles (Bloom, 1985). Recently, two studies (Gould, Lauer, Roman & Pierce, 2005; Wolfenden & Holt, 2005) examined elite junior tennis and proposed parents and coaches fulfil different, and changing, roles over several developmental stages of talent development. Extending these studies to elite professional tennis, the current study was endorsed by the International Tennis Federation (governing body of tennis internationally) and Tennis Australia (governing body of tennis in Australia) to examine professional female tennis players` perceptions of key factors influencing talent identification and development. In doing so, this study identifies effective parenting and coaching approaches associated with talent development in Australian women`s tennis. Methods Ten Australian top ranked Sony-Ericsson Women`s Tennis Association professional tennis players participated in the study by responding to a questionnaire adapted from Wolfenden and Holt`s (2005) interview protocol and designed to address Tennis Australia`s requirements. The questionnaire contained quantitative (5) and qualitative (7) questions, with the latter including asking participants to recall who had introduced them to tennis, how parents and coaches had influenced them to become tennis players and what suggestions they would have for parents and coaches to help develop talent. Data was quantitatively and qualitatively analysed, using descriptive statistics and a series of inductive content analyses (identifying key themes and phrases, or reported verbatim in the words of participants), respectively. Results Participants reported (with one exception) that family members had introduced them to tennis by providing the opportunity and encouragement to play the game. Parents in particular had acted as positive role models, identified talent, and shaped their children`s character in endorsing a competitive spirit. Coaches also played a dominant role in identifying talent and making tennis fun, challenging and competitive. Parents who were supportive, ensured their children had a balanced lifestyle and acted consistently, irrespective of match results were most highly regarded. Those coaches who took an individual and holistic non-judgemental approach with players were most likely to achieve success with their players. Participants nominated an array of suggestions for both parents and coaches to best nurture talent. Discussion This study`s findings support, and extend, previous tennis identification and development research (e.g., Gould et al, 2005). Both parents and coaches were found to play significant roles in stimulating, directing and facilitating a player`s interest in tennis. The professional tennis players who participated in this study highlighted a number of strategies parents and coaches might adopt in successfully `parenting and coaching the talented/gifted player`. In conclusion, the study`s findings suggest a talented player`s journey through to the professional ranks can be a most rewarding experience when player, parent and coach support and complement one another with the player`s well-being and needs to the forefront. Future research may wish to extend investigations to include tennis players across a number of different nationalities as well as male professional players.